Carbon-coated chlorofluorocarbon hydrodechlorination catalyst as well as preparation method and application thereof

By coating platinum and copper nanoparticles in phenolic resin to form a carbon-coated Pt-Cu alloy catalyst, the problems of easy loss of active components of the existing HCFC hydrochlorofluorine dechlorination catalyst are solved, and high activity is achieved , low cost and long life catalyst.

CN119406425AActive Publication Date: 2025-02-11ZHEJIANG UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411498582.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-11
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing HCFC hydrochloric acid dechlorination catalysts have problems such as easy loss of active components and high cost, resulting in poor stability.

Method used

Carbon coating technology is adopted to form a carbon-coated Pt-Cu alloy catalyst by coating platinum and copper nanoparticles in a phenolic resin to improve the stability of the catalyst.

Benefits of technology

It improves the activity and stability of the catalyst, reduces costs, extends the service life of the catalyst, and has great application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005101928450000081
    Figure BDA0005101928450000081
  • Figure BDA0005101928450000091
    Figure BDA0005101928450000091
Patent Text Reader

Abstract

The invention discloses a carbon-coated chlorofluorocarbon hydrodechlorination catalyst and a preparation method and application thereof. The catalyst is prepared by using phenolic resin as a carbon source, platinum as a main catalyst and copper as an auxiliary agent, coating platinum and copper in the carbon source, and calcining and carbonizing in an inert atmosphere; in the catalyst, the loading amount of platinum element is 2-3wt%, and the loading amount of copper element is 8-12%. The preparation method of the carbon-coated Pt-Cu alloy catalyst comprises the following steps: in a phenolic resin reaction system, reducing platinum salt and copper salt in the presence of hydrazine hydrate to obtain Pt-Cu alloy nanoparticles, coating the generated alloy nanoparticles with resin, and carbonizing to obtain the carbon-coated Pt-Cu alloy catalyst. According to the carbon-coated catalyst provided by the invention, the active component is coated inside the carbon material, so that the loss of the active component in the catalyst can be greatly reduced in the reaction process, and the stability of the catalyst is improved, thereby prolonging the service life of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical catalysis, and specifically relates to a carbon-coated fluorochlorocarbon hydrodechlorination catalyst and a preparation method and application thereof. Background Art

[0002] Fluorochlorocarbons (CFCs) are a type of halogenated hydrocarbons composed of chlorine, fluorine and carbon. They are an important class of organic chemicals that are widely used in industrial production and people's daily lives, such as making refrigerants, aerosol propellants, cleaning solvents and foam blowing agents. However, the large-scale use of CFCs will damage the ozone layer in the stratosphere, leading to global climate change. In addition to causing the ozone hole, CFCs, like other volatile chemicals, will dissolve from the atmosphere into environmental water, causing pollution to the soil and groundwater. Therefore, it is very necessary to convert excess CFCs into substances that are clean for the environment.

[0003] Catalytic hydrodechlorination technology (HDC) is a highly promising technology for treating organic chlorinated wastes. It can replace chlorine atoms with hydrogen atoms through a dedicated catalyst, converting harmful chlorine-containing wastes into useful non-toxic products. This method can selectively remove chlorine atoms in CFCs molecules that are destructive to the ozone layer, and convert CFCs into clean products that have no side effects on the environment.

[0004] The current hydrodechlorination catalysts are mainly divided into two categories: non-precious metal catalysts and precious metal catalysts. Hydrodechlorination catalysts are mainly supported catalysts, and the active components mainly include non-precious metals such as Ni, Cr, Cu, and Zn and precious metals such as Ru, Pd, and Pt. The carriers used mainly include different types of activated carbon, silica, alumina, magnesium oxide, silicon carbide, etc.

[0005] CN 105944734 A discloses a catalyst for preparing chlorotrifluoroethylene by catalytic hydrodechlorination of trifluorotrichloroethane and a preparation method thereof, wherein SiO2 particles are used as carriers. Metal Co, Rh, Cr or Mn, KCl or perrhenic acid and Ni are used as active components, and SiO2 particles are impregnated in equal volumes. The catalyst prepared by the method has high catalytic activity and a conversion rate of more than 90%, but poor stability.

[0006] CN 112547070 A discloses a catalyst for preparing chlorotrifluoroethylene and a preparation method thereof. The catalyst carrier is a sintered porous copper-nickel alloy, the active component is Pd, the Pd active component loading is 0.15wt%, the average pore diameter of the sintered porous copper-nickel alloy is 50-300nm, the sintered porous copper-nickel alloy is a hollow structure, and the wall thickness is 0.525mm.

[0007] Supported catalysts are widely used in catalytic reactions, but their stability has always been a key factor restricting their development. Since the active components of supported catalysts are prone to agglomeration and loss during the reaction, the catalyst performance is reduced, limiting its application range.

[0008] In order to solve this problem, carbon-coated metal catalysts have gradually become a hot topic of research. Carbon-coated metal catalysts refer to a layer of carbon material coated on the surface of metal particles to form a core-shell structure. Due to the presence of the carbon layer, the metal particles are isolated from each other in space, which can effectively prevent the metal particles from agglomerating or losing during the reaction and improve the stability of the catalyst. Therefore, inventing a highly active and stable carbon-coated hydrodechlorination catalyst for chlorofluorocarbons is a difficult problem that needs to be solved urgently. Summary of the invention

[0009] In view of the problems existing in the prior art, the present invention provides a carbon-coated hydrodechlorination catalyst for chlorofluorocarbons and a preparation method and application thereof in order to solve the problems of easy loss of active components and high cost of the existing hydrodechlorination catalyst for chlorofluorocarbons. The catalyst has the advantages of high activity, low cost and long life, and has great application prospects.

[0010] The technical solution adopted by the present invention is as follows:

[0011] A carbon-coated hydrodechlorination catalyst for chlorofluorocarbons. The catalyst uses phenolic resin as a carbon source, platinum as a main catalyst, and copper as an auxiliary agent. Platinum and copper are coated inside the carbon source and are calcined and carbonized under an inert atmosphere. The platinum element loading in the catalyst is 2-3wt%, and the copper element loading is 8-12%.

[0012] The method for preparing a carbon-coated fluorochlorocarbon hydrodechlorination catalyst comprises the following steps:

[0013] 1) under vigorous magnetic stirring, cetyltrimethylammonium bromide (CTAB), a soluble platinum salt aqueous solution, a soluble copper salt aqueous solution and deionized water are uniformly mixed, and an excess of hydrazine hydrate is added to carry out a reduction reaction under stirring to reduce the platinum salt and the copper salt to obtain Pt-Cu alloy nanoparticles;

[0014] 2) adding resorcinol and formaldehyde to the reaction solution of step 1), heating the solution to boiling and reflux;

[0015] 3) adding a pH regulator to the reaction solution of step 2) to adjust the pH to alkaline, and continuing to heat to boiling and react under reflux; after the reaction is completed, centrifuging and washing the solution to obtain a catalyst precursor of resin-coated Pt-Cu alloy nanoparticles;

[0016] 4) The catalyst precursor of step 3) is calcined and carbonized under an inert atmosphere to obtain the carbon-coated hydrodechlorination catalyst for chlorofluorocarbons.

[0017] Further, in step 1), the molar concentration of CTAB in the solution is 0.001-0.005 mol / L, the molar amount of hydrazine hydrate is 1.5-8.5 times the total molar amount of the platinum salt and the copper salt, the platinum salt is chloroplatinic acid hexahydrate or potassium chloroplatinite, and the copper salt is copper nitrate trihydrate or copper chloride.

[0018] Furthermore, the dispersed concentrations of platinum salt and copper salt in the reaction solution of step 1) are 0.05-0.1 mg / mL for the Pt element and 0.05-0.35 mg / mL for the Cu element.

[0019] Furthermore, in step 1), the reduction reaction temperature is 20-50° C., and the reaction time is 5-20 min.

[0020] Furthermore, the solid-liquid ratio of resorcinol to formaldehyde in step 2) is 1 g:1.2-1.5 mL, and the mass ratio of resorcinol in step 2) to the Pt element of the platinum salt in step 1) is 50-75:1.

[0021] Furthermore, in step 2), the reflux time under boiling is 10-15 min.

[0022] Furthermore, in step 3), the pH regulator is aqueous ammonia, the mass fraction of which is 25-30%, and the volume amount of which is 0.1-1% of the volume of the deionized water in step 1); and the boiling reflux time in step 3) is 25-40 min.

[0023] Furthermore, in step 3), the inert atmosphere is nitrogen, and the calcination and carbonization are carried out in two steps, the first step is calcination at 250-350° C. for 1-3 h, and the second step is calcination at 650-750° C. for 3-5 h.

[0024] The present invention also provides the use of the carbon-coated hydrochlorofluorocarbon dechlorination catalyst in the catalytic hydrodechlorination of trifluorotrichloroethane to prepare trifluorochloroethylene, the reaction temperature of the catalytic hydrodechlorination is 280-320°C, the feed molar ratio of hydrogen to raw material trifluorotrichloroethane is 1.2-2:1, and the reaction space velocity is 900h -1 .

[0025] The beneficial effects of the present invention are:

[0026] 1) The catalyst preparation method of the present invention is simple, the preparation time is short, and it is easy to operate. Its activity, selectivity and applicability under relatively mild conditions all have significant advantages and good industrial development value. The preparation of the carbon-coated Pt-Cu alloy catalyst of the present invention involves reducing platinum salt and copper salt in the presence of hydrazine hydrate in a phenolic resin reaction system to obtain Pt-Cu alloy nanoparticles, and the generated alloy nanoparticles are coated with resin, and then carbonized to obtain a carbon-coated Pt-Cu alloy catalyst. The carbon-coated catalyst provided by the present invention can greatly reduce the loss of active components in the catalyst during the reaction process, improve the stability of the catalyst, and thus increase the service life of the catalyst because the active components are wrapped inside the carbon material.

[0027] 2) The present invention adopts a carbon coating method instead of a carbon loading method. The presence of the carbon layer isolates the metal particles from each other in space, avoiding the agglomeration and loss of the metal particles during the reaction, thereby ensuring the high stability of the catalyst. The catalyst of the present invention is applied to the reaction system of preparing chlorotrifluoroethylene by catalytic hydrodechlorination of trifluorotrichloroethane, and has the characteristics of high reaction activity, high selectivity and long life, and has great application prospects. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0029] Example 1

[0030] A method for preparing a carbon-coated fluorochlorocarbon hydrodechlorination catalyst comprises the following steps:

[0031] 1) Under vigorous magnetic stirring, 0.12 g of CTAB, 0.53 g of an aqueous solution of chloroplatinic acid with a platinum mass fraction of 4 wt%, 0.42 g of an aqueous solution of copper nitrate with a copper mass fraction of 20 wt%, and 300 ml of deionized water were stirred and mixed in a three-necked flask, 0.40 g of hydrazine hydrate (mass fraction 85%) was added, the mixture was heated to 40° C., and the reaction was carried out for 10 min.

[0032] 2) Add 1.25 g of resorcinol and 1.75 ml of formaldehyde to the reaction solution of step 1), heat the solution to boiling (about 120° C.) and reflux for 10 min, add 1.25 ml of ammonia water (mass fraction 25%), continue to heat the solution to boiling (about 120° C.) and reflux for 40 min, and cool naturally to room temperature.

[0033] 3) The reaction solution of step 2) is centrifuged, washed alternately with ethanol and water three times to obtain a catalyst precursor, and dried at 90°C for 8h. The dried product is carbonized, heated to 300°C at a heating rate of 2°C / min in a nitrogen atmosphere, kept at 300°C for 2h, then heated to 700°C at a heating rate of 2°C / min, kept at 700°C for 4h, and naturally cooled to room temperature to obtain a carbon-coated hydrodechlorination catalyst of chlorofluorocarbons, with a mass of about 1g, and a gas flow rate of 60ml / min during the whole process. According to calculations, the Pt nanoparticle loading in the catalyst is about 2wt%, and the Cu nanoparticle loading is 8wt%.

[0034] Example 2

[0035] The catalyst preparation method is the same as that in Example 1, except that the amount of the copper nitrate aqueous solution with a copper mass fraction of 20 wt% in step 1) is replaced by 0.48 g from 0.42 g, and the other conditions remain unchanged, and finally a carbon-coated hydrodechlorination catalyst for chlorofluorocarbons is obtained. The Pt nanoparticle loading in the catalyst is 2 wt%, and the Cu nanoparticle loading is 9 wt%.

[0036] Example 3

[0037] The catalyst preparation method is the same as that in Example 1, except that the amount of the copper nitrate aqueous solution with a copper mass fraction of 20 wt% in step 1) is replaced by 0.53 g from 0.42 g, and the other conditions remain unchanged, and finally a carbon-coated hydrodechlorination catalyst for chlorofluorocarbons is obtained. The Pt nanoparticle loading in the catalyst is 2 wt%, and the Cu nanoparticle loading is 10 wt%.

[0038] Example 4

[0039] The catalyst preparation method is the same as that in Example 1, except that the amount of the copper nitrate aqueous solution with a copper mass fraction of 20 wt% in step 1) is replaced by 0.58 g from 0.42 g, and the other conditions remain unchanged, and finally a carbon-coated hydrodechlorination catalyst for chlorofluorocarbons is obtained. The Pt nanoparticle loading in the catalyst is 2 wt%, and the Cu nanoparticle loading is 11 wt%.

[0040] Example 5

[0041] The catalyst preparation method is the same as that in Example 1, except that the amount of the copper nitrate aqueous solution with a copper mass fraction of 20 wt% in step 1) is replaced by 0.63 g from 0.42 g, and the other conditions remain unchanged, and finally a carbon-coated hydrodechlorination catalyst for chlorofluorocarbons is obtained. The Pt nanoparticle loading in the catalyst is 2 wt%, and the Cu nanoparticle loading is 12 wt%.

[0042] Example 6

[0043] The catalyst preparation method is the same as that in Example 1, except that the amount of the copper nitrate aqueous solution with a copper mass fraction of 20 wt% in step 1) is replaced by 0 g from 0.42 g, that is, no copper nitrate aqueous solution is added, and the other conditions remain unchanged, and finally a carbon-coated fluorochlorocarbon hydrodechlorination catalyst is obtained.

[0044] Comparative Example 1

[0045] 1) 30g of coconut shell activated carbon with 10-18 mesh was sieved and placed in a three-necked flask. 75ml of nitric acid solution (nitric acid concentration 68%) and 30ml of deionized water were added thereto. The mixture was placed in a constant temperature water bath at 80°C and the speed was set to 500r / min. The mixture was refluxed in the water bath for 6h. After the mixture was washed repeatedly with distilled water until it was neutral, dried at 110°C for 6h, and placed in a desiccator for later use.

[0046] 2) Take 0.53g of chloroplatinic acid solution with a platinum mass fraction of 4wt%, 0.42g of copper nitrate aqueous solution with a copper mass fraction of 20wt% and 1.1g of deionized water, mix them evenly and prepare them as an impregnation solution. Take 1g of the activated carbon treated in step 1) and place it in a beaker, evenly drip the impregnation solution on the activated carbon, perform equal volume impregnation, and impregnate for 15h at room temperature. Dry the impregnated activated carbon at 110°C for 6h to obtain a catalyst precursor. Place the catalyst precursor in a nitrogen atmosphere, heat it from room temperature to 600°C at a rate of 6°C / min, calcine it at 600°C for 2h, and then cool it naturally to room temperature to obtain the desired catalyst. The gas flow rate during the whole process is 60ml / min. The Pt nanoparticle loading in the catalyst is 2wt%, and the Cu nanoparticle loading is 8wt%.

[0047] Comparative Example 2

[0048] The catalyst preparation method is the same as that of Comparative Example 1, except that the amount of copper nitrate aqueous solution with a copper mass fraction of 20wt% in step 1) is replaced by 0.42g to 0.48g, and the amount of deionized water is replaced by 1.1g to 1.04g, and the other conditions remain unchanged, and the catalyst is finally prepared. The Pt nanoparticle loading in the catalyst is 2wt%, and the Cu nanoparticle loading is 9wt%.

[0049] Comparative Example 3

[0050] The catalyst preparation method is the same as that of Comparative Example 1, except that the amount of copper nitrate aqueous solution with a copper mass fraction of 20wt% in step 1) is replaced by 0.53g from 0.42g, and the amount of deionized water is replaced by 0.99g from 1.1g, and the other conditions remain unchanged, and the catalyst is finally prepared. The Pt nanoparticle loading in the catalyst is 2wt%, and the Cu nanoparticle loading is 10wt%.

[0051] Comparative Example 4

[0052] The catalyst preparation method is the same as that of Comparative Example 1, except that the amount of copper nitrate aqueous solution with a copper mass fraction of 20wt% in step 1) is replaced by 0.58g from 0.42g, and the amount of deionized water is replaced by 0.89g from 1.1g, and the other conditions remain unchanged, and the catalyst is finally prepared. The Pt nanoparticle loading in the catalyst is 2wt%, and the Cu nanoparticle loading is 11wt%.

[0053] Comparative Example 5

[0054] The catalyst preparation method is the same as that of Comparative Example 1, except that the amount of copper nitrate aqueous solution with a copper mass fraction of 20wt% in step 1) is replaced by 0.63g from 0.42g, and the amount of deionized water is replaced by 1.42g from 1.1g, and the other conditions remain unchanged, and the catalyst is finally prepared. The Pt nanoparticle loading in the catalyst is 2wt%, and the Cu nanoparticle loading is 12wt%.

[0055] Comparative Example 6

[0056] The catalyst preparation method is the same as in Example 1, except that step 2) is replaced by adding 5 g of sucrose, heating the solution to boiling and refluxing for 40 min. The other conditions remain unchanged, and the catalyst is finally obtained, with a mass of about 1 g. According to calculations, the Pt nanoparticle loading in the catalyst is 2 wt%, and the Cu nanoparticle loading is 8 wt%.

[0057] Comparative Example 7

[0058] The catalyst preparation method is the same as in Example 1, except that step 2) is replaced by adding 1.67 g of aniline, heating the solution to boiling and refluxing for 40 min. The other conditions remain unchanged, and the catalyst is finally obtained, with a mass of about 1 g. According to calculations, the Pt nanoparticle loading in the catalyst is 2 wt%, and the Cu nanoparticle loading is 8 wt%.

[0059] Comparative Example 8

[0060] The catalyst preparation method is the same as in Example 1, except that step 2) is replaced by adding 1.82 g of polyethylene glycol 400, heating the solution to boiling and refluxing for 40 min. The other conditions remain unchanged, and the catalyst is finally obtained, with a mass of about 1 g. According to calculations, the Pt nanoparticle loading in the catalyst is 2 wt%, and the Cu nanoparticle loading is 8 wt%.

[0061] Application Example 1:

[0062] The catalysts prepared in Examples 1-6 and Comparative Examples 1-8 were tested for performance: 1 g of the catalyst was loaded into a reaction tube of a fixed bed catalytic device, the inner diameter of the reaction tube being 15 mm; the temperature was raised from room temperature to 300° C. at a heating rate of 5° C. / min, the molar ratio of hydrogen to raw material trifluorotrichloroethane was 1.5:1, and the reaction space velocity was 900 h -1 The reaction products were analyzed by gas chromatography to calculate the conversion of the reactants and the selectivity of the target olefin products, which are summarized in Table 1.

[0063] Table 1 Conversion rate of trifluorotrichloroethane and selectivity of trifluorochloroethylene over different catalysts

[0064]

[0065]

[0066] By comparing the data of Example 6 with those of Examples 1-5, it can be seen that although the catalyst without the additive has excellent activity at the beginning of the reaction, the catalyst rapidly deactivates as the reaction time increases. The main reason for the catalyst deactivation is carbon deposition. The addition of the copper additive reduces the acid content of the catalyst and inhibits the carbon deposition of the catalyst, thereby improving the catalyst hydrodechlorination performance.

[0067] By comparing the data of Examples 1-5 and Comparative Examples 1-5, it can be seen that although the hydrodechlorination catalyst prepared by the conventional equal volume impregnation method has a high catalytic activity at the beginning of the reaction, after 100 hours of reaction, the catalyst activity decreases significantly and the stability is poor. However, after 100 hours of reaction, the deactivation rate of the carbon-coated hydrodechlorination catalyst of chlorofluorocarbons is much lower than that of the hydrodechlorination catalyst prepared by the impregnation method. The carbon layer effectively reduces the loss of active components and additives in the catalyst and improves the stability of the catalyst.

[0068] By comparing the data of Example 1 and Comparative Examples 6-8, it can be seen that the carbon-coated hydrodechlorination catalyst for chlorofluorocarbons prepared using phenolic resin as a carbon source has a better catalytic activity than other carbon sources.

[0069] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.

Claims

1. A carbon-coated hydrodechlorination catalyst for chlorofluorocarbons, characterized in that: The catalyst uses phenolic resin as a carbon source, platinum as a main catalyst, and copper as an auxiliary agent. Platinum and copper are coated inside the carbon source and are calcined and carbonized under an inert atmosphere. The platinum element loading in the catalyst is 2-3wt%, and the copper element loading is 8-12%.

2. The method for preparing a carbon-coated fluorochlorocarbon hydrodechlorination catalyst according to claim 1, characterized in that: The following steps are involved: 1) Under vigorous magnetic stirring, cetyltrimethylammonium bromide (CTAB), a soluble platinum salt aqueous solution, a soluble copper salt aqueous solution and deionized water are uniformly mixed, and an excess of hydrazine hydrate is added to carry out a reduction reaction under stirring to reduce the platinum salt and the copper salt to obtain Pt-Cu alloy nanoparticles; 2) adding resorcinol and formaldehyde to the reaction solution of step 1), and heating the solution to boiling and reflux; 3) adding a pH adjuster to the reaction solution of step 2) to adjust the pH to alkaline, and continuing to heat to boiling and react under reflux; after the reaction is completed, centrifuging and washing the solution to obtain a catalyst precursor of resin-coated Pt-Cu alloy nanoparticles; 4) The catalyst precursor of step 3) is calcined and carbonized under an inert atmosphere to obtain the carbon-coated hydrodechlorination catalyst for chlorofluorocarbons.

3. The method for preparing a carbon-coated fluorochlorocarbon hydrodechlorination catalyst according to claim 2, characterized in that: In step 1), the molar concentration of CTAB in the solution is 0.001-0.005 mol / L, the molar amount of hydrazine hydrate is 1.5-8.5 times the total molar amount of the platinum salt and the copper salt, the platinum salt is chloroplatinic acid hexahydrate or potassium chloroplatinite, and the copper salt is copper nitrate trihydrate or cupric chloride; the dispersed concentrations of the platinum salt and the copper salt in the reaction solution of step 1) are 0.05-0.1 mg / mL for the Pt element and 0.05-0.35 mg / mL for the Cu element.

4. The method for preparing a carbon-coated fluorochlorocarbon hydrodechlorination catalyst according to claim 2, characterized in that: In step 1), the reduction reaction temperature is 20-50°C and the reaction time is 5-20 min.

5. The method for preparing a carbon-coated hydrodechlorination catalyst for chlorofluorocarbons according to claim 2, characterized in that: The solid-liquid ratio of resorcinol to formaldehyde in step 2) is 1 g:1.2-1.5 mL, and the mass ratio of resorcinol in step 2) to the Pt element of the platinum salt in step 1) is 50-75:

1.

6. The method for preparing a carbon-coated hydrodechlorination catalyst for chlorofluorocarbons according to claim 2, characterized in that: In step 2), the reflux time under boiling is 10-15 minutes.

7. The method for preparing a carbon-coated hydrodechlorination catalyst for chlorofluorocarbons according to claim 2, characterized in that: In step 3), the pH regulator is ammonia water, the mass fraction of which is 25-30%, and the volume amount thereof is 0.1-1% of the volume of the deionized water in step 1); and the boiling reflux time in step 3) is 25-40 minutes.

8. The method for preparing a carbon-coated hydrodechlorination catalyst for chlorofluorocarbons according to claim 2, characterized in that: In step 3), the inert atmosphere is nitrogen, and the calcination and carbonization are carried out in two steps. The first step is calcination at 250-350°C for 1-3h, and the second step is calcination at 650-750°C for 3-5h.

9. Use of the carbon-coated hydrodechlorination catalyst for chlorofluorocarbons as claimed in claim 1 in the catalytic hydrodechlorination of trifluorotrichloroethane to produce trifluorochloroethylene.

10. The use according to claim 9, characterized in that The reaction temperature of catalytic hydrodechlorination is 280-320°C, the molar ratio of hydrogen to raw material trifluorotrichloroethane is 1.2-2:1, and the reaction space velocity is 500-1500 h -1 .

Citation Information

Patent Citations

  • Catalyst for preparing chlorotrifluoroethene from trichlorotrifluoroethane through catalytic hydrodechlorination and preparation method of catalyst

    CN105944734A

  • Catalyst for preparing chlorotrifluoroethylene and preparation method thereof

    CN112547070A

  • Method for synthesizing core-shell structured carbon coated gold nano-particles having spherical morphology by one-step process

    CN108927152A

  • One-dimensional porous platinum-containing alloy nanowire catalyst and preparation method thereof

    CN111509236A

  • High selectivity hydrodechlorination catalyst and preparation method and application thereof

    CN112657507A